2022
DOI: 10.3389/fphar.2022.986510
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin inhibitor LH011 inhibited DSS-induced mice colitis via alleviating inflammation and oxidative stress

Abstract: Background: Ulcerative colitis (UC) is one type of inflammatory bowel disease, characterized by inflammation with infiltration and activation of macrophages in colonic tissue. LH011 is a trypsin inhibitor with potential anti-inflammatory effect.Purpose: Here, we aim to assay the effects of LH011 on UC and further investigate the potential mechanisms in vitro and in vivo.Methods: Dextran sulfate sodium (DSS, 3.5%, w/v) was used to induce UC, and lipopolysaccharide (LPS) was used to induce inflammation in RAW 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In contrast, another study reported MT’s positive outcomes in TNBS (trinitrobenzene sulfonic acid)—induced colitis in mice are mediated by the inhibition of inflammation through the down-regulation of the TLR4/Myeloid differentiation primary response 88 (MyD88)/NF-κB pathway [ 154 ]. Moreover, TLR4 is overexpressed in IBD, and its activation is linked to intestinal inflammation and ulceration [ 155 ]. Conversely, the inhibition of TLR4 signaling by various compounds was associated with improved histological features, with reduced inflammatory cells infiltration, lymphocyte infiltration of lamina propria, mucosal erosion, congestion, edema, and crypt damage in colonic tissue [ 156 , 157 ].…”
Section: Melatonin Involvement In Dysbiosis-associated Conditions Via...mentioning
confidence: 99%
“…In contrast, another study reported MT’s positive outcomes in TNBS (trinitrobenzene sulfonic acid)—induced colitis in mice are mediated by the inhibition of inflammation through the down-regulation of the TLR4/Myeloid differentiation primary response 88 (MyD88)/NF-κB pathway [ 154 ]. Moreover, TLR4 is overexpressed in IBD, and its activation is linked to intestinal inflammation and ulceration [ 155 ]. Conversely, the inhibition of TLR4 signaling by various compounds was associated with improved histological features, with reduced inflammatory cells infiltration, lymphocyte infiltration of lamina propria, mucosal erosion, congestion, edema, and crypt damage in colonic tissue [ 156 , 157 ].…”
Section: Melatonin Involvement In Dysbiosis-associated Conditions Via...mentioning
confidence: 99%
“…[19] Numerous studies have revealed that mitochondrial dysfunction plays an important role in UC. [20–23] Consequently, we can further infer that cuproptosis is strongly linked to UC progression. However, there is a lack of knowledge regarding the mechanisms underlying cuproptosis in the progression of UC.…”
Section: Introductionmentioning
confidence: 95%
“…The activated M1-type macrophages secrete varieties of pro-inflammatory cytokines, such as tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6), which can trigger an inflammatory response and attract other inflammatory cells. , It has also been reported that the M1 macrophages interact with TH1/TH17 cells, further aggravating intestinal epithelial damage . Therefore, targeting macrophage inflammation is one of the crucial strategies in the management of IBD. …”
Section: Introductionmentioning
confidence: 99%